World Association for the Advancement of Veterinary Parasitology (WAAVP) second edition: Guideline for evaluating the efficacy of parasiticides against ectoparasites of ruminants - Holdsworth, Peter; Rehbein, Steffen; Jonsson, Nicholas N.; Peter, Rose; Vercruysse, Jozef; Fourie, Josephus (Veterinary parasitology, 2022)
•The guideline aides planning, conduct, interpretation of ruminant ectoparasiticide efficacy studies.•It provides information on animal selection, dosage determination, confirmation and field studies.•It guides on the conduct of specific studies and provides key information for registration authorities.•It facilitates worldwide adoption of standard study procedures. This second edition guideline was prepared to assist in the planning, conduct and interpretation of studies to assess the efficacy of parasiticides against ectoparasites of ruminants. It provides updated information on the selection of animals, dosage determination, dosage confirmation and field studies, record keeping and result interpretation. This guideline is intended to assist investigators on how to conduct specific studies, to provide specific information for registration authorities involved in the decision-making process, to assist in the approval and registration of new ectoparasiticides, and to facilitate the worldwide adoption of standard procedures.